Multiscale construction of wave-absorbing carbon nanomaterials - Tong Wu; Song Bi; Hao Li; Ruihua Xing; Jun Yang; Xuanyu Liu; Zhuoxun Li (Discover Nano)
Abstract With the gradual improvement of electromagnetic protection of equipment and electromagnetic pollution prevention requirements, carbon heterostructured wave-absorbing nanomaterials have become a research hotspot due to their tunable electromagnetic properties, high stability, and lightweight advantages. In this paper, we comprehensively and deeply discuss the multi-scale construction of carbon nano-absorbent materials, and elaborate on the design strategy and research progress from the micro-, meso- and macro-levels. At the microscopic level, the structure of carbon materials is controlled at the nanoscale by means of intrinsic structural design, elemental doping and interfacial modulation to introduce more microstructural defects to enhance the polarisation and scattering of electromagnetic waves, thereby improving the wave-absorbing performance. The mesoscopic level focuses on the modulation of the micro-nano multilevel structure of carbon absorbers, such as the in situ multilevel assembly of MXene, MOFs and heterogeneous continuous fibers at the mesoscopic scale, which is conducive to the enhancement of the absorber's conductivity and interfacial loss to enhance its wave-absorbing ability. The macroscopic level focuses on structure–function integrated design, such as 3D porous structures, sandwich honeycomb structures, and surface superstructures, which enable the materials to possess excellent mechanical properties along with good wave-absorbing properties. The comprehensive use of these design strategies to optimize the whole design chain of wave-absorbing materials is conducive to maximizing the performance and application value of the materials. The aim of this paper is to elucidate the effect of multiscale heterostructures on carbon-based wave-absorbing materials, which provides a reference for the precise design of their wave-absorbing properties.